Social Media and Elections in Zimbabwe: Twitter War between Pro-ZANU-PF and Pro-MDC-A Netizens - Chibuwe, Albert (Routledge, 2021)
The July 2018 Zimbabwe national elections were characterised by one unique feature: the extensive use of social media especially Twitter, WhatsApp and Facebook, especially by the key presidential contenders Nelson Chamisa and Emmerson Mnangagwa in the struggle for hegemony. The cyber-contestation also became evident between Chamisa’s followers nicknamed “Nerorists” and Mnangagwa’s followers nicknamed “Varakashi.” Fake news and mudslinging became defining elements during these digital propaganda battles. The study, utilising insights from the (digital) public sphere theory and alternative public sphere theory, interrogates the nature of the Twitter war and the “discussions” around key electoral candidates and issues and the implications of the Twitter war on democracy. It further examines how these issues moved from the online platforms to offline spaces. The study concludes that although social media gained prominence in the election, its contribution to democracy is paradoxical. The anonymity and open nature of social media provides an opportunity for participation, but it is precisely this that is also its downside: it provides rooms for emergence of cyber ghosts. The space’s invasion by cyber storm troopers and/or cyber ghosts and netizens serving elite interests undermined social media’s liberative potential as it resulted in irrational “debates,” mudslinging, insults, and outright lies.